Cardiac Glycosides Increase Temozolomide Anticancer Activity in Therapy Resistant Glioblastoma Cells - Anisha Valluri; Logan Lawrence; Krista L. Denning; Jonathan Cuda; Guo-Zhang Zhu (International Journal of Translational Medicine, 2022)
Glioblastomas (GBMs) are a form of malignant gliomas characterized by a dismal prognosis. Standard treatment for glioblastoma patients is combined maximal surgical removal of the tumor with postoperative radiotherapy and concomitant chemotherapy with Temozolomide (TMZ). Among the histological characteristics that contribute to GBM progression are the rapid proliferation and neo-angiogenetic processes. The Na+/K+-ATPase is a transporter that promotes the migration of cancer cells, and its aberrant expression and activity have been associated with several cancers, including GBM. Using cardiac glycosides, we examined the effects of direct inhibition of the Na+/K+-ATPase in glioblastoma cells in vitro. We found that cardiac glycoside Digoxin is an effective anticancer agent on several glioma cell lines via Na+/K+-ATPase inhibition. Drug cytotoxicity assays showed that Digoxin as monotherapy significantly increased cell death and increased the efficacy of Temozolomide (TMZ) in the glioma cell lines T98G, U-97 MG, and primary GBM cells BNC-6. Additionally, Digoxin exhibited important anti-migratory effects on the highly aggressive and chemotherapy-resistant T98G glioma cell-line, demonstrating a potential therapeutic role for cardiac glycosides.